ANTIOXIDANT ACTIVITY, AMINO ACID PROFILE AND MICROBIAL QUALITY OF BEBONTOT, A BALINESE TRADITIONAL FERMENTED CHICKEN MEAT PRODUCTS - I. A., Okarini; Purnomo, H.; ., Aulanni'am; Radiati, L. E. (Majalah Ilmiah Peternakan; Vol 22 No 3 (2019): Vol. 22 No.3 (2019)DO - 10.24843/MIP.2019.v22.i03.p01, 2019)
Antioxidant activity, amino acids profile and microbial quality of raw bebontot of chicken meat of spent laying hen were investigated. The samples were prepared using meat dices (1.5 x 2.0 cm) mixed with fresh ground coriander, garlic, galangal, white pepper, salt, sugar and coconut oil then wrapped in Areca catechu palm dried sheaths and finally fermented spontaneously by drying under the sun for 5 days. The results showed there was a decreasing in pH value, moisture content and 1,1-diphenyl-2-picrylhydrazyl radical scavenging activity of final products, while its total phenolic content was increasing. Glutamic acid was the most abundant amino acid in products after 5 days fementation, followed by tyrosine, aspartic acid, lysine, leucine and histidine. The total plate count and lactic acid bacteria counts were decreasing to 9.39 log cfu/g and 8.98 log cfu/g; the Micrococcaceae was decreased to 5.31 log cfu/g; the yeast and moulds counts were increased to 8.58 log cfu/g and 6.51 log cfu/g at the final stage of fermentation. It can be concluded that bebontot chicken meat in this study is a good source of natural phenolic antioxidant, and the present microorganisms will provide the source for the selection of strains well adapted to the environment and able to compete with contaminant bacteria.